Dimensional changes of the post extraction alveolar ridge, preserved with Leukocyte- and Platelet Rich Fibrin: A clinical pilot study. (September 2016) - Anwandter, Andreas; Bohmann, Stephanie; Nally, Mauricio; Castro, Ana B.; Quirynen, Marc; Pinto, Nelson
Abstract: Objectives: This clinical trial explored the clinical and radiographic dimensional changes of the alveolar ridge in the first 4 months after tooth extraction in combination with the application of Leukocyte- and Platelet Rich Fibrin (L-PRF). Methods: Eighteen single rooted maxillary and mandibular sockets were filled with L-PRF without soft tissue closure. Clinical measurements (bone sounding) were performed using a customized acrylic stent and radiographic measurements were accomplished using Cone Beam Computed Tomography (CBCT), immediately after tooth extraction and after 4 months. Results: The clinical observations indicated a mean horizontal resorption of 1.18 ± 2.4 mm (p = 0.8) at the crest, 1.25 ± 2.0 mm (p = 0.57) and 0.83 ± 2.0 mm (p = 0.78) at 2 mm and 4 mm apical to the crest, respectively. The buccal plate demonstrated a mean vertical loss of 0.44 ± 3.5 mm (p = 0.9), the centre of the socket had a significant filling of 5.72 ± 3.6 mm (p = 0.0001) and the oral cortical plate had a mean vertical gain of 0.09 mm ± 1.57 mm (p = 0.9). The radiographic analysis demonstrated a mean vertical bone loss of 0.27 ± 2.5 mm (p = 0.9) on the buccal and of 0.03 ± 1.6 mm (p = 0.9) at the oral crest. The width of the alveolar ridge had a mean loss of 1.33 mm ± 1.43 mm. Conclusions: Within the limitations of this pilot study, it can be concluded that L-PRF might show clinical benefits for ridge preservation.